SUITABILITY OF PLACEMENT AND ORGANIZATIONAL CLIMATE TO WORK EFFECTIVENESS BY MEDIATING INDIVIDUAL CHARACTERISTICS - Handayani, Rin; Sutianingsih, Sutianingsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to understand how individual characteristics play an important role in mediating the relationship between job placement, organizational climate and work effectiveness. In this study, quantitative research methods were used. Data were collected with the help of questionnaires and a sample of 30 workers. Path analysis and descriptive analysis are the data analysis methods used. Research findings show that all variables positively influence from 1) job placement and organizational climate have an impact on individual characteristic variables. 2) Work placement, organizational climate and individual characteristics have an impact on work effectiveness. 3) The results of this study state that the indirect influence of individual characteristic variables can influence job placement variables and organizational climate and work effectiveness. Keywords: individual characteristics, organisational climate, work effectiveness, work placement.